Algorithmic Annotation of Functional Roles for Components of 3,044 Human Molecular Pathways - Sorokin, Maxim; Borisov, Nicolas; Kuzmin, Denis; Gudkov, Alexander; Zolotovskaia, Marianna; Garazha, Andrew; Buzdin, Anton (Frontiers in Genetics, 2021)
Current methods of high-throughput molecular and genomic analyses enabled to reconstruct thousands of human molecular pathways. Knowledge of molecular pathways structure and architecture taken along with the gene expression data can help interrogating the pathway activation levels using different bioinformatic algorithms. In turn, the pathway activation profiles can characterize molecular processes which are differentially regulated and give numeric characteristics of the extent of their activation or inhibition. However, different pathway nodes may have different functions towards overall pathway regulation, and calculation of pathway activation level requires knowledge of molecular function of every node in the pathway in terms of its activator or inhibitory role. Thus, high-throughput annotation of functional roles of pathway nodes is required for the comprehensive analysis of the pathway activation profiles. We proposed an algorithm that identifies functional roles of the pathway components and applied it to annotate 3044 human molecular pathways extracted from the Biocarta, Reactome, KEGG, Qiagen Pathway Central, NCI, and HumanCYC databases and including 9022 gene products. The resulting knowledgebase can be applied for the direct calculation of the pathway activation levels and establishing large scale profiles of the signaling, metabolic and DNA repair pathway regulation using high throughput gene expression data. We also provide a bioinformatic tool for pathway activation level data calculations using the current pathway knowledgebase.